Peroneus brevis split tear – A challenging diagnosis: A pictorial review of magnetic resonance and ultrasound imaging – Part 2: Imaging with magnetic resonance and ultrasound - Katarzyna Bokwa-Dąbrowska; Dan Mocanu; Isaac Romanus; Rafał Zych; Michael Huuskonen; Pawel Szaro (European Journal of Radiology Open)
Peroneal tendon pathology is common among physically active individuals, with tenosynovitis, tendon subluxation, split tears and rupture. However, diagnosing these conditions, particularly peroneus brevis split tears, is clinically and radiologically challenging. Magnetic resonance imaging (MRI) and ultrasound (US) can sometimes miss split tears. A significant portion of peroneus split tears develops on a background of tendinopathy. The presence of tenosynovitis, changes in tendon shape, and multiple subtendons can indicate a complete multifragmenting split tear. A defect on the surface of the tendon may indicate a partial-thickness split tear, commonly referred to as the ''cleft sign.'' Peroneus subluxation is particularly likely when the superior peroneal retinaculum is torn. Given the subtlety of clinical symptoms, radiological evaluation is essential. Dynamic US assessment is especially valuable for detecting instability and split tears. This pictorial review presents the imaging spectrum of the most common pathologies of the peroneus brevis tendon on US and MRI.